2022
DOI: 10.15678/eber.2022.100204
|View full text |Cite
|
Sign up to set email alerts
|

How small printing firms alleviate impact of pandemic crisis? Identifying configurations of successful strategies with fuzzy-set qualitative comparative analysis

Abstract: The objective of this article is to identify strategies that can help small firms alleviate the negative impact of the Covid-19 crisis. We tested six strategies (namely, entrepreneurial, market penetration, market development, product development, diversification, and cooperation). In particular, we identified combinations of these strategies that may lead to performance during the current pandemic crisis. Research Design & Methods: This is a quantitative study that uses fuzzy-set qualitative comparative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…According to research by Cetera (2020), some companies in the industry used this form of support when crisis response funds became available, and some were planning to apply for it. A significant change in the business conditions for printing companies was the loosening of restrictions that took place in June 2020 (Suder et al, 2022). It was then that cultural and sports institutions reopened; these constitute a significant part of the customer base for printing companies.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to research by Cetera (2020), some companies in the industry used this form of support when crisis response funds became available, and some were planning to apply for it. A significant change in the business conditions for printing companies was the loosening of restrictions that took place in June 2020 (Suder et al, 2022). It was then that cultural and sports institutions reopened; these constitute a significant part of the customer base for printing companies.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…It is primarily due to these last factors (which have been sources of global crises over the last three years) that academia has expressed a gradual increase in crisis management, with a particular emphasis on behaviors that are related to the changes and adjustments of business strategies as responses to changing environmental conditions (Pusceddu, Moi & Cabiddu, 2022;Suder, Kusa, Duda & Dunska, 2022;Puumalainen, Sjögrén, Soininen, Syrjä & Kraus, Vonmetz, Orlandi, Zardini & Rossignoli, 2023;. The crisis that was caused by the COVID-19 pandemic (which began in late 2019) has become a particularly appropriate context for research on entrepreneurial strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner (2011) found that company size matters in the context of a propensity to introduce environmental training. In turn, Graafland et al (2003) note that large companies are more likely to use formal CSR reporting, while small and medium-sized companies employ informal ways (Suder, Kusa, Duda, & Dunska, 2022) to manage activities related to CSR, such as daily communication.…”
Section: Company Size and Internal Communicationmentioning
confidence: 99%
“…The Covid-19 pandemic served to accelerate digitalization processes and proved that only the newest high-tech solutions make it possible to function in crisis conditions (Banaszyk et al, 2021;González-Tejero et al, 2022;Suder et al, 2022). Hashai et al, (2022):…”
Section: Introductionmentioning
confidence: 99%